2017
DOI: 10.4254/wjh.v9.i32.1210
|View full text |Cite
|
Sign up to set email alerts
|

Role of pregnane X-receptor in regulating bacterial translocation in chronic liver diseases

Abstract: Bacterial translocation (BT) has been impeccably implicated as a driving factor in the pathogenesis of a spectrum of chronic liver diseases (CLD). Scientific evidence accumulated over the last four decades has implied that the disease pathologies in CLD and BT are connected as a loop in the gut-liver axis and exacerbate each other. Pregnane X receptor (PXR) is a ligand-activated transcription factor and nuclear receptor that is expressed ubiquitously along the gut-liver-axis. PXR has been intricately associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 157 publications
(214 reference statements)
0
14
0
1
Order By: Relevance
“…Since PXR has been demonstrated to play an important role in protecting the barrier in intestinal or liver disease 17,23 , we investigated whether PXR also plays a role in NEC pathogenesis. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PXR has been demonstrated to play an important role in protecting the barrier in intestinal or liver disease 17,23 , we investigated whether PXR also plays a role in NEC pathogenesis. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the MAPK pathway could affect tight junctions and cause dysfunction of the intestinal barrier 23,25,26 , we further examined whether PXR could regulate MAPK pathway signaling. After Caco-2 cells were treated with LPS at 5 μg/ml for 30 min, we observed increased phosphorylation of Erk and p38 and a notable increase in phospho-JNK levels (Fig.…”
Section: Pxr Could Inhibit the Phosphorylation Of Jnkmentioning
confidence: 99%
“…Intestinal TJ proteins play an important function in maintaining gut barrier and in restricting bacterial translocation to the liver and the systemic circulation. 86,87 One study revealed elevated levels of circulating bacteria and bacterial endotoxins beta-glucan and lipopolysaccharide (LPS) in severely ill patients with SARS-CoV-2 infection. 88 The regulation of TJ proteins is facilitated through nuclear receptors such as Pregnane X receptor, whose activation was seen to confer preserved TJ proteins 87 and protect against bacterial translocation in cirrhosis.…”
Section: Disruption Of Tight Junction Protein a Potential Mechanismentioning
confidence: 99%
“…As the MAPK pathway could affect tight junctions and cause dysfunction of the intestinal barrier 23,25,26 , we further examined whether PXR could regulate MAPK pathway signaling. After Caco-2 cells were treated with LPS at 5 µg/ml for 30 min, we observed increased phosphorylation of Erk and p38 and a notable increase in phospho-JNK levels (Fig.…”
Section: Activation Of Pxr Improved Barrier Function In Caco-2 Cellsmentioning
confidence: 99%